The role of tumor-associated macrophages in lung cancer - Zhu, Ronghao; Huang, Jing; Qian, Fenhong (Frontiers in Immunology, 2025)
Lung cancer remains a leading cause of cancer-related deaths worldwide, necessitating innovative treatments. Tumor-associated macrophages (TAMs) are primary immunosuppressive effectors that foster tumor proliferation, angiogenesis, metastasis, and resistance to therapy. They are broadly categorized into proinflammatory M1 and tumor-promoting M2 phenotypes, with elevated M2 infiltration correlating with poor prognosis. Strategies aimed at inhibiting TAM recruitment, depleting TAMs, or reprogramming M2 to M1 are therefore highly promising. Key signaling pathways, such as CSF-1/CSF-1R, IL-4/IL-13–STAT6, TLRs, and CD47-SIRPα, regulate TAM polarization. Additionally, macrophage-based drug delivery systems permit targeted agent transport to hypoxic regions, enhancing therapy. Preclinical studies combining TAM-targeted therapies with chemotherapy or immune checkpoint inhibitors have yielded improved responses and prolonged survival. Several clinical trials have also reported benefits in previously unresponsive patients. Future work should clarify the roles of macrophage-derived exosomes, cytokines, and additional mediators in shaping the immunosuppressive tumor microenvironment. These insights will inform the design of next-generation drug carriers and optimize combination immunotherapies within precision medicine frameworks. Elucidating TAM phenotypes and their regulatory molecules remains central to developing novel strategies that curb tumor progression and ultimately improve outcomes in lung cancer. Importantly, macrophage-based immunomodulation may offer expanded treatment avenues.